Procalcific Phenotypic Drift of Circulating Progenitor Cells in Type 2 Diabetes with Coronary Artery Disease. (28th February 2012) - Fadini, Gian Paolo; Albiero, Mattia; Menegazzo, Lisa; Boscaro, Elisa; Agostini, Carlo; Vigili de Kreutzenberg, Saula; Rattazzi, Marcello; Avogaro, Angelo
Abstract : Diabetes mellitus (DM) alters circulating progenitor cells relevant for the pathophysiology of coronary artery disease (CAD). While endothelial progenitor cells (EPCs) are reduced, there is no data on procalcific polarization of circulating progenitors, which may contribute to vascular calcification in these patients. In a cohort of 107 subjects with and without DM and CAD, we analyzed the pro-calcific versus endothelial differentiation status of circulating CD34+ progenitor cells. Endothelial commitment was determined by expression of VEGFR-2 (KDR) and pro-calcific polarization by expression of osteocalcin (OC) and bone alkaline phosphatase (BAP). We found that DM patients had significantly higher expression of OC and BAP on circulating CD34+ cells than control subjects, especially in the presence of CAD. In patients with DM and CAD, the ratio of OC/KDR, BAP/KDR, and OC+BAP/KDR was about 3-fold increased than in other groups. EPCs cultured from DM patients with CAD occasionally formed structures highly suggestive of calcified nodules, and the expression of osteogenic markers by EPCs from control subjects was significantly increased in response to the toll-like receptor agonist LPS. In conclusion, circulating progenitor cells of diabetic patients show a phenotypic drift toward a pro-calcific phenotype that may be driven by inflammatory signals.